Glial amino acid transporters - Ortega, Arturo; Schousboe, Arne (Springer, 2017)
Our current knowledge of the role of macroglia in the physiology of the nervous system has been shaped on by both the established role of oligodendrocytes and Schwann cells in the propagation of the action potential and by the concept of the tripartite synapse. In both cases, integral membrane proteins such as receptors and transporters are crucial for the proper function of these cells. This book is an extensive review of the contribution of glial membrane transporters. Model transporters are analysed in terms of their structure, distribution and involvement in major functions and/or pathologies of the nervous system. It is important to note that a particular emphasis has been placed in the rather unexplored signalling properties of glial transporters. Likewise, strategies toward the design of novel compounds that target membrane transporters are discussed. Different points of view of the involvement and contribution of glial transporters are presented in this volume, and the contrast of these interpretations invites the readers to broaden their interest of membrane transporters beyond the chapters of this book. No intention was made to provide a certain order to the chapters of the book; in fact any of them can be read independently. We want to express our appreciation to the contributors for their enthusiasm in the preparation of their excellent chapters that will certainly provide a fresh perspective of the exponential accumulation of knowledge that has been published in the last few years and unequivocally changing the concept of glial physiology. It is our hope that this book provides a major input to the fascinating field of membrane transporters as fundamental proteins for the establishment of a better understanding of glia-neuron interactions.
Includes index.
Keywords: GABA.; Glutamic acid.; elektronické knihy; electronic books